2019
DOI: 10.1109/tasc.2018.2889463
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Current Switch for HTS Superconducting Magnets: Design, Control Strategy, and Test Results

Abstract: High temperature superconductor (HTS) is becoming more and more attractive for the application in high field magnets which can be utilized in the magnetic resonance imaging (MRI) and rotating machines. To charge the HTS magnets and operate them in persistent current mode, a persistent current switch (PCS) is very necessary. This paper will focus on how to build a fast persistent current switch controlled by AC magnetic field. The PCS can present a large resistance rapidly compared with conventional PCS and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Numerous studies have shown that bulk superconductors and stacks of HTS tapes are capable of trapping magnetic fields of several teslas or higher and can therefore be used as pseudopermanent trapped field magnets (TFMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The range of potential practical applications of such magnets extends from magnetic bearings and levitation devices to motors and highfield magnets [1,2,16,[19][20][21][22][23]. For example, TFMs made from magnetized stacks of HTS tapes have been shown to provide higher levitation forces compared to bulks [24], whereas bulk HTSs look very promising for the development of compact high-torque rotating machines [18].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that bulk superconductors and stacks of HTS tapes are capable of trapping magnetic fields of several teslas or higher and can therefore be used as pseudopermanent trapped field magnets (TFMs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The range of potential practical applications of such magnets extends from magnetic bearings and levitation devices to motors and highfield magnets [1,2,16,[19][20][21][22][23]. For example, TFMs made from magnetized stacks of HTS tapes have been shown to provide higher levitation forces compared to bulks [24], whereas bulk HTSs look very promising for the development of compact high-torque rotating machines [18].…”
Section: Introductionmentioning
confidence: 99%
“…The DC current, I dc , is first injected to the spiral tape or the CORC cable via a ramp function, I r (t), and Dirichlet boundary condition is used for I r (t), as given in Eq. (7).…”
Section: Numerical Modelling a T-a Formulationmentioning
confidence: 99%
“…Rare-Earth Barium Copper Oxide (REBCO) hightemperature superconducting (HTS) coated conductors become promising candidates for power applications, such as rotating machines [1], [2], [3], flux pumps [4], [5] and persistent current switches [6], [7], [8], due to their excellent in-field critical current performance. In those HTS devices,…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] carried out investigation on the working principle of the transformer-rectifier HTS flux pump. [34][35][36][37][38][39] proposed different types of switches to improve the behavior in charging speed. [40][41][42][43][44][45] discussed the characteristics of the dynamic resistance, which determines the working performance of flux pump.…”
Section: Introductionmentioning
confidence: 99%